2010
DOI: 10.1007/s10815-010-9394-7
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and morphometric analysis of the ultrastructure of human oocytes cryopreserved by two alternative slow cooling protocols

Abstract: Purpose To ascertain possible cell damage from cryopreservation, the ultrastructure of human oocytes cryopreserved by slow cooling was assessed. Materials and methods Cryopreservation was performed through two protocols with one-step or two-step propanediol. Fresh control oocytes were examined for comparison. Samples were processed for transmission electron microscopy analysis. Results By light microscopy, both fresh and frozen-thawed oocytes appeared regularly rounded, with intact zona pellucida, and homogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 43 publications
9
35
1
3
Order By: Relevance
“…Many studies reported that, cryopreservation can affect subcellular structure of oocytes such as chromosomes, spindle, plasmalemma, cortial granules, mitochondria, and so on [20][21][22]. ΔΨm is one of the most sensitive indices of freezing injury.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported that, cryopreservation can affect subcellular structure of oocytes such as chromosomes, spindle, plasmalemma, cortial granules, mitochondria, and so on [20][21][22]. ΔΨm is one of the most sensitive indices of freezing injury.…”
Section: Discussionmentioning
confidence: 99%
“…After 2-5 days at 4°C, the samples were processed for light microscopy (LM) and TEM examination as described in [18][19][20]22].…”
Section: Light/electron Microscopymentioning
confidence: 99%
“…In humans, vacuoles may occur commonly in response to a cellular injury, as for example in procedures of oocyte cryopreservation at MII stage [17][18][19][20]22].…”
Section: Ooplasmic Aggregatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytoplasmic vacuolization is one of the most common signs of damage in cryopreserved oocytes (Nottola et al 2009;Coticchio et al 2010) and ovarian tissue ) and has been adopted as a specific marker for cryodamage (Coticchio et al 2010). Silva et al (2000) have suggested that damage to smooth endoplasmic reticulum (ER) leads to vacuolization.…”
Section: Introductionmentioning
confidence: 99%